Exploring the role of school assumptions and artefacts in building sustainable and prosperous secondary schools - Sithole, Mukateko Louisa (STAI Miftahul Ula Nganjuk, 2025)
This study explores how school assumptions and artefacts contribute to building sustainable and prosperous secondary schools. Guided by an interpretive paradigm and qualitative approach, data were collected through semi-structured interviews with six purposively selected participants from a high-performing secondary school. Thematic analysis revealed that shared assumptions, such as religion, equality, commitment, and professionalism, shape school culture and promote sustainability. Key artefacts, including school uniforms, sports, ceremonies, and logos, reinforced identity, pride, and discipline. The study recommends embedding shared assumptions into school practices, leveraging artefacts purposefully, promoting holistic development, and fostering stakeholder partnerships to support sustainable school environments.